2021
DOI: 10.1111/cen.14465
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative prediction of granulation pattern subtypes in GH‐secreting pituitary adenomas

Abstract: Objective The aim of this study was to establish a preoperative prediction method for sparsely granulated (SG) growth hormone (GH)‐secreting pituitary adenoma, an aggressive tumour subtype with high recurrence risk, in acromegaly patients. Methods Eighty‐three patients with GH‐secreting pituitary adenomas were included in this study. GH measurements, cytokeratin immunostaining and electron microscopy were performed to detect granulation patterns. Preoperative factors, including general, radiological and endocr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
2
4
0
1
Order By: Relevance
“…This makes the comparison of our results with others complicated. In our cohort, SG tumors occurred more frequently in younger patients compared to DG tumors, which complies with the previous literature [6,[21][22][23][24]. The cited authors showed that diagnosis or operation age in patients with SG tumors ranged from 36 to 44 years, wherein the majority of them were indicated as being over 40 years and below 44 years.…”
Section: Discussionsupporting
confidence: 91%
“…This makes the comparison of our results with others complicated. In our cohort, SG tumors occurred more frequently in younger patients compared to DG tumors, which complies with the previous literature [6,[21][22][23][24]. The cited authors showed that diagnosis or operation age in patients with SG tumors ranged from 36 to 44 years, wherein the majority of them were indicated as being over 40 years and below 44 years.…”
Section: Discussionsupporting
confidence: 91%
“…On the one hand, this value represents a quantification of the difficulty of total resection during transsphenoidal surgery. Patients with residual tumors have a greater risk of progression postoperatively according to previous studies ( 5 , 15 18 ). The relapse rate was higher after 10 years of follow-up than after only 5 years of follow-up in patients with a residual tumor.…”
Section: Discussionmentioning
confidence: 84%
“…With the development of artificial intelligence and data science, many studies have used radiomics methods or machine learning to predict the recurrence of brain tumors (18,21,22). However, models built by those methods lack universality between different study centers due to the heterogeneity of data collection, which is the key to the accuracy of model building.…”
Section: Discussionmentioning
confidence: 99%
“…Sparsely granulated tumour cells have characteristic juxtanuclear fibrous bodies, in over 70% of cells, with a histological dot-like appearance ( Mete & Lopes 2017 ). Sparsely granulated somatotroph tumours have been associated with larger size, invasiveness, aryl hydrocarbon receptor-interacting protein (AIP) mutations, lower SSTR2 expression and poor response to somatostatin receptor ligands ( Brzana et al 2013 , Heng et al 2021 , Swanson et al 2021 ). Clinically silent somatotroph tumours are more frequently sparsely granulated ( Chinezu et al 2017 ).…”
Section: Who Classificationmentioning
confidence: 99%